DAWAH AND TABOO WORD: A SOCIOLINGUISTIC STUDY ON ISLAMIC LECTURES BY MADURESE KYAIS - Fatmawati Fatmawati (Universitas 17 Agustus 1945 Surabaya, 2021)
Dawah and taboo words are generally considered as two contradict things. However, there is a possibility to hear taboo words in dawah. Therefore, this article aims to study taboo words used by Madurese Kyais in their Islamic lectures. The study uses descriptive qualitative method. The data are Youtube videos of Islamic lectures by Madurese Kyais. There are four videos chosen based on some criteria. The findings show that all four Madurese Kyais mention taboo words in their Islamic lectures. The taboo words can be categorized into swear or curse words, obscene words, four-lettered words, dirty words, and animal names. All of them can be used as humor, but only swear word can be used to persuade people and obscene words, dirty words, and animal names to describe something.